2017
DOI: 10.3168/jds.2017-12971
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Relationship between methods for measurement of serum electrolytes and the relationship between ionized and total calcium and neutrophil oxidative burst activity in early postpartum dairy cows

Abstract: The objectives of this study were to (1) compare a test for serum measurement of total Ca (tCa), Mg, and P (VetTest Chemistry Analyzer, IDEXX Laboratories Inc., Westbrook, ME) to reference methods (spectrophotometric assays on a Beckman Coulter 640e automated clinical chemistry analyzer; Beckman Coulter, Brea, CA), (2) determine the relationship between ionized Ca (iCa) and reference method tCa in the immediate postpartum period, and (3) assess the relative value of these blood Ca indices as predictors of neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 20 publications
5
45
2
2
Order By: Relevance
“…It has been suggested that iCa 2+ can be a more sensitive predictor of functional outcomes associated with postpartum calcium status. That study showed a more consistent association between iCa 2+ and in vitro neutrophil function compared with total serum Ca 2 in early postpartum cows . Blood iCa 2+ concentration is generally measured using conventional blood gas analyzers in veterinary diagnostic laboratories, which might not be suitable for field practitioners and those in farm settings.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been suggested that iCa 2+ can be a more sensitive predictor of functional outcomes associated with postpartum calcium status. That study showed a more consistent association between iCa 2+ and in vitro neutrophil function compared with total serum Ca 2 in early postpartum cows . Blood iCa 2+ concentration is generally measured using conventional blood gas analyzers in veterinary diagnostic laboratories, which might not be suitable for field practitioners and those in farm settings.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, iCa 2+ concentrations measured by the i‐STAT were regressed on iCa 2+ concentrations measured by the Radiometer ABL800 FLEX to determine curvilinearity. Lastly, receiver operating characteristic curves were developed at iCa 2+ cutoff concentrations of <1.00 and <1.18 mmol/L (subclinical hypocalcemia) to assess Se and Sp of the i‐STAT at the highest Youden index . A P of < 0 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium status can be measured directly using either total Ca or ionized Ca concentrations in blood. Although ionized Ca is considered to be the more biologically active fraction and recent work (Leno et al, 2017) suggests that ionized Ca concentrations are more consistently related to neutrophil function in vitro than total Ca, research also suggests that the relationship between ionized Ca and total Ca varies in the days after calving (Ballantine and Herbein, 1991;Leno et al, 2017) and thus cannot be used interchangeably as indicators of Ca status. Notably, the large observational studies referenced above relating Ca status with postpartum outcomes related to disease, milk production, and reproduction all used total Ca as their indicator, and ionized Ca has received limited evaluation as a predictor of these outcomes.…”
Section: Bloodmentioning
confidence: 99%
“…In clinical situations, the animals might not be able to maintain normal concentrations of these constituents in blood, thus substantially changing the correlation between tCa and iCa concentrations (Toffaletti, 1989). Leno et al (2017) demonstrated that the relationship between whole-blood iCa and serum tCa differed by sampling time point after calving. Additionally, these authors showed that iCa measurements were more consistently related to outcomes of neutrophil oxidative burst activity measured in vitro.…”
Section: Calcium Metabolismmentioning
confidence: 97%
“…Additionally, these authors showed that iCa measurements were more consistently related to outcomes of neutrophil oxidative burst activity measured in vitro. Therefore, wholeblood iCa concentrations likely correlate with the clinical syndrome associated with abnormal Ca status (Lincoln and Lane, 1990;Leno et al, 2017).…”
Section: Calcium Metabolismmentioning
confidence: 99%